2018
DOI: 10.1177/1129729818792826
|View full text |Cite
|
Sign up to set email alerts
|

Nurse performed peripheral intravenous catheter first time insertion success in pediatric patients in Bhutan: An observational study

Abstract: Introduction: Peripheral intravenous catheter insertion is a clinical procedure commonly performed by nurses for pediatric patients in Bhutan. This study describes peripheral intravenous catheter first attempt success and factors associated with such insertions. Methods: A cross-sectional survey was conducted from October 2016 to March 2017, comprised of a national sample of the Bhutan pediatric patient population (0-12 years). We collected data on peripheral intravenous catheter first time insertion success r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(45 citation statements)
references
References 10 publications
4
36
0
5
Order By: Relevance
“…The rate of difficult IV access decreased as age increased in many studies with consistent results. [4][5][6][7][8][9][10] Our study also showed a similar tendency with statistical significance. A history of prematurity has been evaluated in a few studies.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The rate of difficult IV access decreased as age increased in many studies with consistent results. [4][5][6][7][8][9][10] Our study also showed a similar tendency with statistical significance. A history of prematurity has been evaluated in a few studies.…”
Section: Discussionsupporting
confidence: 81%
“…The correlation between vein visibility and palpability and difficult IV access has been shown in several studies. 5,7,9,10,16 Moreover, several assist devices, such as an ultrasound-guide and infrared vein visualization devices, are utilized to improve the success rate of peripheral IV catheter placement at the PED. 17,18 Although vein visibility and palpability are not significantly related to difficult IV access, the tendency of visibility and palpability toward successful IV access are present, and we still recommend using assist devices, especially in difficult cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, in most situations, children with non-cyanotic congenital heart disease have good exposure of peripheral veins, which prevents the ultrasound method from showing its advantage of visualization compared with the traditional landmark method. The success rate of the rst attempt was used as one of the crucial metrics by many studies to evaluate the effectiveness of peripheral venipuncture [3,16]. But no consistent conclusions have been drawn about the in uence of the use of ultrasound on the success rate at the rst attempt of peripheral venous access.…”
Section: Discussionmentioning
confidence: 99%
“…Delayed venous access may lead to unexpected adverse events. The success rate for peripheral venipuncture had been reported with varying results in infants and toddlers using the traditional anatomical landmark approach, with the overall success rate ranging from 30-64% [1][2][3].…”
mentioning
confidence: 99%